Manfaat Tantangan dan Interaksi Personal dalam Proses Pembelajaran Anak di Era AI - Reva Fadilla; Sariva Aulia Rabani; Gusmaneli (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The development of artificial intelligence (AI) technology has brought significant changes to various aspects of life, including education. In the context of elementary school learning, AI is beginning to be utilized as a tool to improve the effectiveness of the teaching and learning process. The main issues addressed in this research are how AI can provide benefits in improving learning effectiveness, the challenges that arise in its implementation in elementary school environments, and efforts to maintain personal interactions between teachers and students amidst the use of technology. The purpose of this study is to determine the impact of AI use on students' learning experiences and the role of teachers in creating a balanced learning environment between technology and the human touch. The research method used a qualitative descriptive approach with a case study plan, and data collection techniques through literature review and limited field observations. The results indicate that AI can support a more interactive, personalized, and efficient learning process. However, the main challenges faced are limited infrastructure, teacher digital competency, and the potential reduction in direct social interaction. Therefore, collaboration between teachers, students, and technology is crucial to creating an optimal learning process.